Assessment of origin and fate of contaminants along mining-affected Rio Montevecchio (SW Sardinia, Italy): A hydrologic-tracer and environmental mineralogy study. (October 2019) - De Giudici, Giovanni; Medas, Daniela; Cidu, Rosa; Lattanzi, Pierfranco; Rigonat, Nicola; Frau, Ilaria; Podda, Francesca; Marras, Pier Andrea; Dore, Elisabetta; Frau, Franco; Rimondi, Valentina; Runkel, Robert L.; et al.
Abstract: Hydrologic tracer techniques were applied to Rio Montevecchio (SW Sardinia, Italy), a stream affected by mine drainage, allowing the calculation of discharge and contaminant loads. Discharge along the stream showed a constant increase throughout the 2.7 km-long study reach, up to 13.6 l/s at the last synoptic point. Calculated loads of mine-related constituents were large, reaching values of 1780 kg/day for SO 4 2 −, 340 kg/day for Zn, 47 kg/day for Fe, and 50 kg/day for Mn. The difference of the cumulative instream metal loads between the first and the last synoptic sampling points indicated gains of 421 kg/day for Zn, 2080 kg/day for SO 4 2 −, 56 kg/day for Mn, and 50 kg/day for Fe. The source areas critical for contaminants loading were almost all concentrated in the first 800 m of the stream, with the exception of Pb, whose loading occurs evenly along the whole study reach. Precipitation of secondary minerals along the streambed was responsible for a very high attenuation of Al and Fe loads (66% and 77%) and affected also SO 4 2 − and Zn loads, though less effectively. Rio Montevecchio has the second highest metal load among the rivers investigated with tracer techniques in SW Sardinia. In comparison with Rio Irvi, which has one order of magnitude higher metal loads, natural attenuation processes limit the loads in Rio Montevecchio. Results are useful to clarify the hydrogeochemical paths involved in the release and attenuation of pollutants, improving our understanding of stream responses to contamination and aiding development of site-specific remediation actions. Highlights: Rio Montevecchio transports metal loads among the highest amidst Sardinian streams. Dispersed underground sources are critical for the dispersion of contaminants. Attenuation processes reduce aluminium and iron loads. Fe-oxyhydroxides, jarosite and amorphous Al(OH)3 precipitate along the stream.